2018
DOI: 10.18388/abp.2017_1622
|View full text |Cite
|
Sign up to set email alerts
|

Non-histone nuclear protein HMGN2 differently regulates the urothelium barrier function by altering expression of antimicrobial peptides and tight junction protein genes in UPEC J96-infected bladder epithelial cell monolayer

Abstract: The urinary tract is vulnerable to frequent challenges from environmental microflora. Uropathogenic Escherichia coli (UPEC) makes a major contribution to urinary tract infection (UTI). Previous studies have characterized positive roles of non-histone nuclear protein HMGN2 in lung epithelial innate immune response. In the study presented here, we found HMGN2 expression was up-regulated in UPEC J96-infected urothelium. Surprisingly, over-expression of HMGN2 promoted disruption of BECs 5637 cells' intercellular j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In several instances, the isolated alpha-helical domain peptide of HMGN2 has been shown to possess the same antimicrobial activity as full length HMGN2 [81]. In addition, HMGN2 seems to induce autophagy, a novel antimicrobial pathway, and protects bladder epithelial cells from infection by E. coli and other Gram-negative bacteria [82][83][84]. In agreement, recent studies indicated that deficiency in HMGN2 affected macrophage polarization and non-tuberculosis mycobacterial survival in macrophages [85].…”
Section: Immune Functionssupporting
confidence: 54%
“…In several instances, the isolated alpha-helical domain peptide of HMGN2 has been shown to possess the same antimicrobial activity as full length HMGN2 [81]. In addition, HMGN2 seems to induce autophagy, a novel antimicrobial pathway, and protects bladder epithelial cells from infection by E. coli and other Gram-negative bacteria [82][83][84]. In agreement, recent studies indicated that deficiency in HMGN2 affected macrophage polarization and non-tuberculosis mycobacterial survival in macrophages [85].…”
Section: Immune Functionssupporting
confidence: 54%
“…Not much is known about vitamin D in the context of tight junction proteins in the urinary tract. However, uropathogenic Escherichia coli (UPEC) infection disrupts the tight junction barrier with downregulation of occludin and claudins in bladder epithelial cells (Tian et al 2018). Similarly, during interstitial cystitis syndrome, occludin is downregulated (Lee and Lee 2014).…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, it has been found that UPEC infection disrupts the tight binding barrier with decreased expression of TJ proteins. 10 Therefore, any strategy designed to strengthen the urothelial barrier would decrease the risk of urinary tract infection. 11 Consuming cranberry (Vaccinium macrocarpon) has been reported as a nonantibiotic prophylactic and therapeutic alternative for recurrent UTI.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the case of the bladder, it has been reported that the urothelium permeability increases as the expression of TJ proteins decreases, allowing the entry/passage of bacteria as well as the passage of ions through the blood-urinary barrier . In addition, it has been found that UPEC infection disrupts the tight binding barrier with decreased expression of TJ proteins . Therefore, any strategy designed to strengthen the urothelial barrier would decrease the risk of urinary tract infection …”
Section: Introductionmentioning
confidence: 99%